Factual narratives and the real in therapy and psychoanalysis - Scheidt, Carl Eduard; Stukenbrock, Anja (Narrative factuality, 2020)
Das Kapitel Factual Narratives and the Real in Therapy and Psychoanalysis erschien in Narrative Factuality auf Seite 297.
Gesehen am 14.02.2022